Review on temperate oak decline and oak diseases with a focus on Germany - Gitta Jutta Langer; Johanna Bußkamp; Katharina Burkhardt; Rainer Hurling; Pavel Plašil; Martin Rohde (Journal für Kulturpflanzen)
An overview of temperate oak decline and diseases with their different causes is given with special reference to Germany.We discuss the most important complex diseases of oak, i.e. acute oak decline and chronic oak decline, and diseases with a predominantly single cause (sudden oak death, root rot, Phytophthora diseases, and Oak powdery mildew), and the important insect pests oak leaf-feeding caterpillars, jewel beetle infestations. The damage patterns and the associated biotic and abiotic factors are analysed in terms of predisposing, triggering, and accompanying factors. The current damage processes, especially in north-western Germany, are presented and compared with known disease patterns in oak. The influences of the European megadrougth 2018, which is interpreted as an effect of climate change, are discussed. An example is the vitality loss of oak associated with the occurrence of Diplodia corticola. Finally, general recommendations for the management of the most important biotic pests, especially Agrilus biguttatus, and the affected oak stands are given.